Le Défi De La Scolarisation Primaire Universelle Des Filles Dans La Région Du Worodougou En Côte D’Ivoire - Yeo Soungari; Kei Mathias (European Scientific Journal, ESJ, 2016)
Under-education and schooling are important phenomena that hinder the achievement of universal primary education, especially for girls. This article aims to analyze strategies to implement in order to achieve universal primary education for girls in the region of Worodougou, in northwestern of Côte d’Ivoire. To collect data, individual and group interviews were conducted with actors of education. After this investigation, it is concluded that the obstacles to achieving of this goal are, among others, poverty, illiteracy of the parents, social representation of women in the community, migration of girls from Worodougou region, in particular, the dream of going to settle in the west countries, and more specifically in France, etc. The proposed strategies are numerous. However, we can mention the need for the implementation of literacy programs, effectiveness of free education for all the children, increasing educational opportunities, etc.